The Unaccented Vowels of Proto-Norse. - Syrett, Martin (North-Western European language evolution. Supplement., 1994)
The Unaccented Vowels of Proto-Norse attempts to analyse the unaccented vowel system attested in the proto-Norse period, as partially attested in the older runic inscriptions in the elder futhark. Each chapter in turn assesses the evidence for unaccented syllables of a particular category, whether inflectional or derivational, and decides whether any reliable conclusions can be drawn from it. It is argued that too many widely accepted views are based on insufficient and poor methodology, and that too little note has been taken of the fact that viable alternatives exist alongside most of our th.